Customer managed intermodal transport solutions: why, how, for whom?. (1st January 2013) - Jensen, Arne; Sorkina, Edith
The study investigates development of new intermodal transport solutions with specific focus on solutions where customers, the shippers, choose to develop and manage their own intermodal solutions instead of buying the transport service in the market. The purpose of the paper is to study the design aspects of customer managed intermodal transport system development to see what makes such systems competitive. Focus is on why shippers develop such solutions; how they solve fundamental performance problems; and what characterises such shippers. Shippers engage in development and management of intermodal solutions based on perceived weak signals about future threats and opportunities. Intermodal solutions are designed to meet cost, quality, and environmental requirements. Shippers engaging in development of such solutions have large and concentrated flows. Furthermore, they have strong environmental policies, and are highly dependent on efficient transport. Finally, they are major buyers in the transport market having previous experience in using rail/intermodal.